NUCLEAR BAN TREATY: CAN IT UNRAVEL THE GLOBAL NON-PROLIFERATION REGIME? (Journal of Contemporary Studies, 2018)
Abstract The Treaty on Prohibition of Nuclear Weapons (TPNWs) was negotiated with the primary purpose of creating a new international norm that could bring pressure upon all the nuclear possessor states to work towards nuclear disarmament. Instead, the TPNW may have led to more divisions between thenuclear weapon states (NWS) and the non-nuclear weapon states (NNWS) that could affect the outcome of the 2020 NPT (Nuclear Non-proliferation Treaty) Review Conference. Parallel initiatives with conflicting obligations, spearheaded by the nongovernmental organizations (NGOs) and negotiated amongst the NNWS mainly, without taking into consideration security interests of all states, are likely to reduce the incentive for the nuclear possessor states (both NPT and the non-NPT states) to remain constructively engaged with the non-proliferation regime, thus making the goal of nuclear disarmament more elusive.